Comprehensive and evolutionary analysis of Spodoptera litura-inducible Cytochrome P450 monooxygenase gene family in Glycine max elucidate their role in defense - Yadav, Manisha; Panwar, Ruby; Rustagi, Anjana; Chakraborty, Amrita; Roy, Amit; Singh, Indrakant K.; Singh, Archana (Frontiers in Plant Science, 2023)
Plants being sessile organisms and lacking both circulating phagocytic cells and somatic adaptive immune response, have thrived in various defense mechanisms to fend off insect pests and invasion of pathogens. CYP450s are the versatile enzymes which thwart plants against insect pests by ubiquitous biosynthesis of phytohormones, antioxidants, and secondary metabolites, utilizing them as feeding deterrents and direct toxins. Therefore, a comprehensive analysis of biotic stress-responsive CYPs from Glycine max was performed to ascertain their function against S. litura-infestation. Phylogenetic analysis, evolutionary conserved domains and motifs disclosed the evolutionary correspondence of these GmCYPs with already characterized members of the CYP450 superfamily and close relatedness to Medicago truncatula. These GmCYPs have evolved due to tandem duplication, possess 1-8 exons, mapped on 13 chromosomes and localized in endoplasmic reticulum mostly. Further, identification of methyl-jasmonate, salicylic acid, defense responsive and flavonoid biosynthesis regulating cis-acting elements, their interaction with biotic stress regulating proteins and their differential expression in diverse types of tissues, and during herbivory, depicted their responsiveness to biotic stress. Three-dimensional homology modelling of GmCYPs, docking with heme cofactor required for their catalytic activity and enzymesubstrate interactions were performed to understand the functional mechanism of their action.Moreover, to gain insight into their function in plant defense, gene expression analysis was evaluated which revealed differential expression of 11 GmCYPs upon S. litura infestation, 12GmCYPs on wounding while foliar spray of ethylene, methyl-jasmonate and salicylic acid hormone differentially regulate 11 GmCYPs, 6 GmCYPs, and 10 GmCYPs respectively Our study comprehensively analyzed the underlying mechanism of GmCYPs function during S. litura infestation, which can be further utilized for functional characterization to develop new strategies for enhancing soybean resistance to insect pests.